2021
DOI: 10.3390/molecules27010083
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2-Thioxoimadazolidin-4-one Derivatives as Potent Anti-Cancer Agents through Apoptosis Induction and Antioxidant Activation: In Vitro and In Vivo Approaches

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most widespread malignancies and is reported as the fourth most prevalent cause of cancer deaths worldwide. Therefore, we aimed to investigate the probable mechanistic cytotoxic effect of the promising 2-thioxoimidazolidin-4-one derivative on liver cancer cells using in vitro and in vivo approaches. The compounds were tested for the in vitro cytotoxic activity using MTT assay, and the promising compound was tested in colony forming unit assay, flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
(61 reference statements)
4
11
0
Order By: Relevance
“…Figure 5 shows that the compound treatment increased the cell population by 46.32% in pre-G phase compared to 2.19% in the control and by 46.12% in S phase compared to 33.61% in the control, while the cell population was not significantly decreased. These findings are consistent with previous studies [38], which evaluated apoptosis-inducing activity using flow cytometric apoptosis and cell cycle analyses.…”
Section: • Cell Cycle Analysissupporting
confidence: 93%
“…Figure 5 shows that the compound treatment increased the cell population by 46.32% in pre-G phase compared to 2.19% in the control and by 46.12% in S phase compared to 33.61% in the control, while the cell population was not significantly decreased. These findings are consistent with previous studies [38], which evaluated apoptosis-inducing activity using flow cytometric apoptosis and cell cycle analyses.…”
Section: • Cell Cycle Analysissupporting
confidence: 93%
“…With treatment of copper complex of 2-Thioxo Imidazolidin-4-Ones as antioxidants, antioxidant levels were significantly increased to (0.074) and it was observed that GSH was increased to (0.075), Catalase was increased to (0.068), These results are in accordance with (Nafie et al,2021) antioxidant levels were significantly increased, Because the treatment caused the regulation of apoptosis.…”
Section: Resultssupporting
confidence: 75%
“…The discovery of new effective anti-inflammatory agents, thus, considered as an urgent concern [ 4 , 5 ]. Several reports demonstrated 2-thioxoimidazolidine-4-one analogues as a potent class of compounds which possess a broad-spectra of pharmacological and biological activities [ 64 , 65 , 66 ]. Among synthesized and evaluated compounds, compound 5 and 7 exhibited the most potent cytotoxic activity against LPS-activated RAW264.7 cells (IC 50 of 212.3 μg/mL and 197.68 μg/mL, respectively), comparable to that of celecoxib drug (IC 50 value 251.2 μg/mL) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cycling conditions were initial heating stage 5 min at 95 °C, then 45 cycles of denaturation phase at 95 °C 10 s, annealing phase at 60 °C 30 s, and extension phase at 72 °C 1 min using iScript TM One-Step RT-PCR Kit with SYBR ® Green (Bio-Rad, Hercules, CA, USA). Finally, the expression of relative gene was carried out using 2 −ΔΔct equation and normalized to β-actin gene [ 66 , 97 ]. Primers of IL-6 were F 5′-AGACAGCCACTCACCTCTTCAG-3′, R 5′-TTCTGCCAGTGCCTCTTTGCTG-3′; primers of TNF-α were F 5′-CTCTTCTGCCTGCTGCACTTTG-3′, R 5′-ATGGGCTACAGGCTTGTCACTC-3′; primers of β-actin were F 5′-GCACCACACCTTCTACAATG-3′, R 5′-TGCTTGCTGATCCACATCTG-3′.…”
Section: Methodsmentioning
confidence: 99%